From Rationalism to Cognitive Science: the Science that Makes the Man Human - Cabrera, Marcos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
Cognitive science has evolved significantly, and recently it has achieved big changes in the philosophical thinking that when referred to scientific field, now it allows us to indagate more about the science generation process, and also to know better how scientific theories are chosen; something that has been understood by philosophers as a mere rational process with no place for emotions, but nowadays we can tell that has changed significantly and is giving scientists their right place as humans more than logical entities.